1999
DOI: 10.1038/sj.neo.7900048
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Tumor Cell Proliferation in Animal Models

Abstract: Revealing the mechanisms of neoplastic disease and enhancing our ability to intervene in these processes requires an increased understanding of cellular and molecular changes as they occur in intact living animal models. We have begun to address these needs by developing a method of labeling tumor cells through constitutive expression of an optical reporter gene, and noninvasively monitoring cellular proliferation in vivo using a sensitive photon detection system. A stable line of HeLa cells that expressed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(141 citation statements)
references
References 21 publications
4
136
0
Order By: Relevance
“…Models of photon diffusion through tissue have indicated that as few as one hundred bioluminescent cells should be detectable at subcutaneous tissue sites, and approximately 10 6 cells would be required to generate signals that are detectable through two cm of tissue (52). These predictions by Rice et al (52) were made with the assumption of a light output of 30 photons per cell per second at a wavelength of 650 nm, and have largely been supported empirically through a number of studies using different tumor cells at various tissue sites (5,37,43,(53)(54)(55). The levels of reporter gene expression in a given cell type will determine the extent to which it can be detected in vivo.…”
Section: Overview Of Optical Imaging Using Bioluminescencementioning
confidence: 71%
See 1 more Smart Citation
“…Models of photon diffusion through tissue have indicated that as few as one hundred bioluminescent cells should be detectable at subcutaneous tissue sites, and approximately 10 6 cells would be required to generate signals that are detectable through two cm of tissue (52). These predictions by Rice et al (52) were made with the assumption of a light output of 30 photons per cell per second at a wavelength of 650 nm, and have largely been supported empirically through a number of studies using different tumor cells at various tissue sites (5,37,43,(53)(54)(55). The levels of reporter gene expression in a given cell type will determine the extent to which it can be detected in vivo.…”
Section: Overview Of Optical Imaging Using Bioluminescencementioning
confidence: 71%
“…Whole-body imaging of light that is generated within the body and transmitted through tissue is an exciting approach for studying biological processes in laboratory animals. Reporter genes that encode either fluorescent or bioluminescent proteins have been used to create internal biological light, and these reporter genes have been used broadly in the study of small animal models of human biology and disease (37,(41)(42)(43)(44). In the study of neoplasia, these strategies have enabled longitudinal studies of the disease course from minimal disease states to late stages of disease.…”
Section: Overview Of Optical Imaging Using Bioluminescencementioning
confidence: 99%
“…12,13 Then, metastatic processes in vivo were investigated by using B16-BL6 cells stably expressing luciferase (BL6-luc cells). Pulmonary metastasis in living mice was evaluated with the in vivo imaging system.…”
Section: Resultsmentioning
confidence: 99%
“…Non-invasive optical techniques for monitoring firefly luciferase 1,2 and green fluorescent protein (GFP) [3][4][5] expression in living animals have been developed and applied to in vivo gene transfer models. Luciferase and GFP in vivo imaging techniques provide the advantages of non-invasive and repetitive monitoring of reporter gene expression in living animals, but are primarily qualitative/semi-quantitative and do not provide tomo-graphic images.…”
Section: Introductionmentioning
confidence: 99%